Using Advanced Instructional Technology To Enhance Pesticide Applicator Training Programs - Michael J. Weaver; Patricia A. Hipkins; William F. Murphy; Glen H. Hetzel (Journal of Applied Communications, 1991)
As public concern over the use of pesticides grows, the need for properly trained applicators becomes more important.